The Impact of Parental Depressive, Anxiety, and Stress Symptoms on Adolescents’ Mental Health and Quality of Life: The Moderating Role of Parental Rejection - Eirini Sofrona; Georgios Giannakopoulos (Children)
Background/Objectives: Parental internalizing issues, particularly maternal mental health, can significantly influence adolescents’ mental health by altering parenting behaviors and roles. This study explores the role of parental rejection in moderating the relationship between parental depressive, anxiety, and stress symptoms and adolescents’ mental health and quality of life. Methods: One hundred thirty eight mothers (mean age: 47.96, SD = 5.06 years) and 68 fathers (mean age: 51.07, SD = 5.53 years) of adolescents aged 12–18 completed measures on mental health, parental rejection, and adolescent well-being. Results: Maternal rejection was found to moderate the relationship between maternal anxiety symptoms and adolescents’ quality of life, as well as between maternal anxiety symptoms and adolescents’ mental health problems. Paternal rejection moderated the relationship between paternal stress symptoms and adolescents’ mental health. However, parental rejection did not moderate the relationship between parental depression and adolescents’ quality of life or mental health. Conclusions: These findings highlight the distinct roles of maternal and paternal rejection in adolescent development and suggest that parental mental health, particularly anxiety and stress, has a significant impact on adolescent well-being. Future studies should consider the influence of both parents and focus on longitudinal effects. These results emphasize the need for interventions addressing parental rejection to improve adolescent outcomes.